1998
DOI: 10.1007/s11746-998-0227-0
|View full text |Cite
|
Sign up to set email alerts
|

Determination of iodine value of palm oil based on triglyceride composition

Abstract: The triglyceride (TG) composition of palm oil is normally determined by high-performance liquid chromatography (HPLC). The HPLC chromatograms indicated a good separation of most of the TG components in the oil. The TG can be classified based on either the TG groups, i.e., triunsaturated, monosaturated, disaturated, or trisaturated, or the number of double bonds, i.e., zero, one, two, three, or four double bonds. The more unsaturated the fatty acid, the greater the iodine value (IV). Therefore, it is hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 6 publications
0
32
0
1
Order By: Relevance
“…The drift tube temperature, nebulizer power, and gas pressure of the ELS detector were set at 45°C, 60% (heating), and 35 psi, respectively. TAG peaks were identified based on the retention time of TAG standards and the results of Haryati et al [22] All TAG proportions are given in percentage area. The IV of PS and all fractions was analyzed using Wijs solution according to AOCS official method Cd 1-25.…”
Section: Chemical Characterizationmentioning
confidence: 99%
“…The drift tube temperature, nebulizer power, and gas pressure of the ELS detector were set at 45°C, 60% (heating), and 35 psi, respectively. TAG peaks were identified based on the retention time of TAG standards and the results of Haryati et al [22] All TAG proportions are given in percentage area. The IV of PS and all fractions was analyzed using Wijs solution according to AOCS official method Cd 1-25.…”
Section: Chemical Characterizationmentioning
confidence: 99%
“…Foreign fats can be determined in lard by Boemer number method (11) which is based on the difference between melting points of TAGs and the fatty acids, which is large in pure pork fat and small for others such as beef tallow fats. Haryati et al (12), found that differences in TAG group composition in fats are reflected on the DSC thermograms. Guillen and Cabo (13) used the FTIR spectroscopy to characterize edible oil and lard.…”
Section: Jaswir Mes Mirghani Th Hassan Et Almentioning
confidence: 99%
“…To reduce the use of toxic solvent, cyclohexane 3,4) has been substituted as a replacement for chloroform in Wijs method but longer reaction time is required especially for oils with higher IV. Other reported alternative methods with minimum solvent consumption were flow injection analysis (FIA) 5) , Fourier transform infrared spectroscopy (FTIR) 6) , near infrared spectroscopy (NIR) 7,8) , 1 H nuclear magnetic resonance spectroscopy ( 1 H NMR) 9) , differential scanning calorimetry (DSC) 10) and high performance liquid chromatography (HPLC) 11,12) . DSC was the first reported thermal method for IV determination in palm oil.…”
Section: Introductionmentioning
confidence: 99%